The interconnecting web: Adult learning cohorts as sites for collaborative learning, feminist pedagogy and experiential ways of knowing. - Randee Lipson Lawrence (Adult Education Research Conference, 1997)
This paper describes research conducted to understand and given meaning to the experience of adults learning in cohort groups, in non-traditional graduate and undergraduate degree programs in higher education. The researcher sought to enter into the lived world of the learners to view the experience from their perspective.